1978
DOI: 10.2165/00003088-197803020-00004
|View full text |Cite
|
Sign up to set email alerts
|

Diseases and Drug Protein Binding

Abstract: In a number of pathological states a decrease in the plasma protein binding of drugs is observed. This may be due to many factors related either to the protein, or the ligand (drug), or to the binding conditions. The most important of these disease states quantitatively are probably hypoalbuminaemia, conditions resulting in modification of the albumin compartment volume and the presence on albumin binding sites of pathological inhibitors of drug binding. A decrease in the extent of drug plasma protein binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(40 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…However, there seems to be a paucity of knowledge regarding the protein binding of basic drugs in nephrotic syndrome (Gugler & Azarnoff, 1976;Tillement et al, 1978;Piafsky, 1980). We have recently shown that the protein binding of a basic drug, disopyramide, in plasma from clinically stable or well-controlled nephrotic patients was not significantly different from that in the normal healthy controls (Echizen et al, 1986) despite the fact that the serum albumin levels in these nephrotic patients (mean ± s.d., 26 ± 5 g 1-1) were substantially lower than those in the controls (45 ± 4 g l-1).…”
mentioning
confidence: 94%
“…However, there seems to be a paucity of knowledge regarding the protein binding of basic drugs in nephrotic syndrome (Gugler & Azarnoff, 1976;Tillement et al, 1978;Piafsky, 1980). We have recently shown that the protein binding of a basic drug, disopyramide, in plasma from clinically stable or well-controlled nephrotic patients was not significantly different from that in the normal healthy controls (Echizen et al, 1986) despite the fact that the serum albumin levels in these nephrotic patients (mean ± s.d., 26 ± 5 g 1-1) were substantially lower than those in the controls (45 ± 4 g l-1).…”
mentioning
confidence: 94%
“…Impaired plasma protein binding of drugs in patients with kidney and liver disease is well recognized (reviewed by Reidenberg, 1976;Jusko & Gretch, 1976;Blaschke, 1977;Tillement, Lhoste & Giudicelli, 1978). No such information is available for the antirheumatic drug azapropazone which is strongly bound to plasma proteins (Breuing, Gilfrich, Meinertz & Jahnchen, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The situation seems to be even more complicated in patients with liver disease (Affrime & Reidenberg, 1975;Klotz, 1976;PerezMateo & Erill, 1977;Blaschke, 1977;Tillement et al, 1978 (Schmidt & Jahnchen, 1979). The binding of azapropazone to albumin was determined using a commercially available human serum albumin preparation (dried, purified, electrophoretic purity 100%; Behringwerke AG, Marburg, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…This decrease may be ascribed to the higher NEFA concentration in those subjects in spite of a net increase in AAG concentration (Table 6) (Baruzzi et al, 1986;Pedersen et al, 1987). Acute renal failure is known to increase NEFA concentrations (Tillement et al, 1978) and NEFA have an affinity for albumin (Ka= 107-108 M-1) greater than that of many drugs and so can inhibit their binding to albumin (Rudman et al, 1971). This is so for acidic drugs (Bowmer & Lindup, 1982) and also for basic drugs (Brown et al, 1981;Horiuchi et al, 1989;Kessler et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the fu value of tianeptine in cirrhotic patients could be accounted for by the decrease in HSA concentration (Tillement et al, 1978). The major mechanism for this reduced binding seems to be impaired protein synthesis and/or the presence of endogenous binding inhibitors (Klotz et al 1976;Thiessen et al, 1976).…”
Section: Discussionmentioning
confidence: 99%